If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x(2) + -6 = 74 Reorder the terms for easier multiplication: 4 * 2x + -6 = 74 Multiply 4 * 2 8x + -6 = 74 Reorder the terms: -6 + 8x = 74 Solving -6 + 8x = 74 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 8x = 74 + 6 Combine like terms: -6 + 6 = 0 0 + 8x = 74 + 6 8x = 74 + 6 Combine like terms: 74 + 6 = 80 8x = 80 Divide each side by '8'. x = 10 Simplifying x = 10
| 4n^2-7=249 | | M(2)+7=6 | | 6x^2-5=481 | | B(2)=34 | | A(2)+1=2 | | 8km^2p*3mn^3= | | 3n^2-10=17 | | X(2)=29 | | 3x-4y+2z+5x+2y-3z= | | R(2)=96 | | 2cd*cd= | | 4x+3+8-3x=-2x+6x-2 | | 30x+4=244 | | 3p^2+10=310 | | 4hk*5st= | | 3mn*9m= | | 2,5/x=8/3 | | 2x+3y+0.1z=100 | | 7x-3y+2x-10y= | | 4x-24=3x+36 | | -4fgh^2*(-2gh)= | | 6w^2+9w+2=0 | | 9=2r+r | | .33x-2=.25x+3 | | 3pq*2pr= | | 5y-11=24whatisy | | 5y-11=24wgatisy | | 2(x+1)+x=7 | | cos(36+x)+cos(x)=0 | | cosx(36+x)+cos(x)=0 | | 0.5D^2+1.5D+1=0 | | tan*x=0.625 |